Análisis de la política nacional de seguridad alimentaria en Colombia, una mirada desde los programas de desarrollo Rural 2007-2014 (2017)
This article presents an analysis of the evolution and creation of the national policy of Food and Nutrition Security in Colombia (SAN). Also, an analysis of the Rural Development Plans Secure Agricultural Income - Rural Development with Equity (AIS-DRE) applied by the national government during the 2007-2014 period, in order to examine the relationship of policies aimed at developing the agricultural variety of food availability as main variable explaining the condition of National Food Security. For this relationship, three variables that explain the state in national agricultural production is tom. The agricultural production, harvested area and yield, and compared with three variables that reflect the condition of National Food Security.